2022
DOI: 10.3390/en15093277
|View full text |Cite
|
Sign up to set email alerts
|

Differential Genetic Mechanisms of Deep High-Quality Reservoirs in the Paleogene Wenchang Formation in the Zhu-1 Depression, Pearl River Mouth Basin

Abstract: The Lufeng Sag and Huizhou Sag, both located in the Zhu-1 Depression, have similar geographical locations, but their reservoir characteristics in the Paleogene Wenchang Formation show obvious differences. Primary intergranular pores are mainly developed in the Lufeng Sag. However, secondary pores are the main reservoir space in the Huizhou depression. Overall, the reservoir properties of the Lufeng Sag are better than those of the Huizhou Sag. To analyse the differences between the Paleogene reservoirs in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The South China Sea (SCS) is at the convergence of the Pacific Plate (Philippines Sea Plate), the Indo-Australian Plate, and the Eurasian Plate. It records the interaction among multiple surrounding plates and has been considered a natural laboratory for studying the tectonic evolution of marginal seas [28][29][30][31][32]. However, the origin of the SCS remains obscure, and four principal tectonic models have been proposed for SCS opening: (1) slab pull from subduction of a proto-South China Sea; (2) extrusion tectonics from the India-Asia collision; (3) basal drag from a mantle plume; and (4) backarc rifting [33][34][35][36][37][38].…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…The South China Sea (SCS) is at the convergence of the Pacific Plate (Philippines Sea Plate), the Indo-Australian Plate, and the Eurasian Plate. It records the interaction among multiple surrounding plates and has been considered a natural laboratory for studying the tectonic evolution of marginal seas [28][29][30][31][32]. However, the origin of the SCS remains obscure, and four principal tectonic models have been proposed for SCS opening: (1) slab pull from subduction of a proto-South China Sea; (2) extrusion tectonics from the India-Asia collision; (3) basal drag from a mantle plume; and (4) backarc rifting [33][34][35][36][37][38].…”
Section: Geological Settingmentioning
confidence: 99%
“…Additionally, a NE-striking depression-controlling fault, known as the Zhu III South Fault, governed the formation of the Zhu III Depression as a half-graben, with faulting in the south and overlapping in the north. Given the development of en echelon folds, horsetail faults, and oblique steps in the Wenchang Sag, it is revealed that the Zhu III South Fault has undergone dextral strike-slip deformation [10,15,25,26,32]. Except the boundary fault, it has also been revealed that strike-slip activity occurred along the faults within the depression.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations